Restricting the voltage-dependent optical response of a GEVI to lipid rafts reveals an alternate conformation depending on lipid environment - Lee, Haeun; Frankiv, Nazarii; Park, Eugene; Baker, Bradley J. (BIOPHYSICAL JOURNAL, 2024)
Altering the amino acid composition of the voltage-sensing domain (VSD) of a genetically-encoded voltage indicator (GEVI) yielded a discontinuous optical response when the plasma membrane potential was changed despite uniform membrane expression. This novel GEVI, Anpak I, fuses a modified VSD from the voltage-sensing phosphatase gene family to a fluorescent protein to optically report voltage transients across the plasma membrane. Anpak I trafficks well to the plasma membrane, but only yields a voltage-dependent optical signal at discreet subsections of the plasma membrane. Other sections are optically quiet. A second GEVI, Anpak II, utilizes the VSD from the GEVI Bongwoori fused to a fluorescent protein mutated to increase the flexibility of the chromophore. Anpak II exhibits two distinct voltage-dependent optical signals: one that resembles the activity and spatial patterning of Anpak I, and the other resembling the activity of the original Bongwoori signal. Together, these results demonstrate that the lipid environment of the plasma membrane can alter the conformation of membrane proteins thereby potentially influencing their functional activities. In addition, Anpak I and Anpak II can be used to identify different lipid compositions based on the voltage response of the GEVI. This research is funded by KIST (2E32162).